2009
DOI: 10.1590/s0303-76572009000100010
|View full text |Cite
|
Sign up to set email alerts
|

Alterações auditivas em trabalhadores de indústrias madeireiras do interior de Rondônia

Abstract: O ruído ocupacional é considerado um risco físico bastante freqüente em quase todos os segmentos industriais e, desse modo, merece atenção especial por parte dos profissionais da saúde e segurança do trabalho. O presente estudo investigou a presença de queixas e alterações audiométricas em trabalhadores de indústrias madeireiras do interior de Rondônia. Participaram do estudo 16 trabalhadores de três indústrias, os quais foram submetidos a uma entrevista sobre a audição, bem como ao exame audiológico por meio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
(2 reference statements)
0
5
0
4
Order By: Relevance
“…The survey was done with 83 male workers, what can be observed in other researches with workers who are exposed to occupational noise 8,13,14,15,16 , in which is the most occurring sex.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The survey was done with 83 male workers, what can be observed in other researches with workers who are exposed to occupational noise 8,13,14,15,16 , in which is the most occurring sex.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies related to the auditory and non-auditory complaints of workers 3,8,14,19 point tinnitus as the most reported complaint by the subjects exposed to occupational noise. This symptom is increasingly present in the population due to various factors, such as increasing exposure to high sound pressure levels, in the occupational environment, lifestyle, eating habits, overwork, stress, anxiety and depression…”
mentioning
confidence: 99%
“…There is (20) that assessed 53 workers from three lumbering companies and found audiometry results of 31.25% with audiometric notch, in which 13.5% suggested NIHL and 6.25% had other audiometric alterations. Moreover, a study carried out in a lumbering company in Distrito Industrial de Maracanaú, in Ceará (21) with 25 workers, where the authors found altered audiometric results in 24% of them.…”
Section: Discussionmentioning
confidence: 99%
“…Francisca Pinheiro Fontoura (1) , Cláudia Giglio de Oliveira Gonçalves (2) , Adriana Bender Moreira de Lacerda (3) , Herton Coifman (4) It is a crosscut study developed at the laundry of a large Public Federal Hospital located in Curitiba/ Parana State, Brazil, from May to December/2010, having hospital laundry workers as the research subjects. A total of 95 noise-exposed workers, participated in the study (57.89 % females and 42.11% males), age ranging 20 to 59 years (averaging 38.…”
Section: Efeitos Do Ruído Na Audição De Trabalhadores De Lavanderia Hmentioning
confidence: 99%
“…In relation to the necessary time exposition for triggering noise-induced hearing loss, the highest number of impairing rates occurs between five and seven years, decreasing loss progression rate until fifteen years when it tends to stabilize as long as exposition conditions and absence of other causative factors are kept 2,4,5 . Noise-induced hearing loss characterized by irreversible cochlear damage, in configuration of high-frequency features one of the most serious, prevalent problems for workers' health.…”
mentioning
confidence: 99%